On the secrecy performance of RIS-enabled wireless communications over Nakagami-m fading channels - Ashutosh K. Yadav; Suneel Yadav; Anshul Pandey; Adão Silva (ICT Express, 2023)
This paper examines the secrecy performance of reconfigurable intelligent surface aided wireless communication systems. Specifically, we derive the secrecy outage probability (SOP), intercept probability, probability of non-zero secrecy capacity, and ergodic secrecy capacity (ESC) expressions over Nakagami-m fading channels. We further evaluate the asymptotic SOP expressions to get some insights into the secrecy diversity order under two scenarios of interest; (1) when the signal-to-noise ratio approaches infinity, and (2) when the main-to-eavesdropper ratio tends to infinity. Also, we analytically show the effect of reflecting element density on the ESC performance. The numerical and simulation studies verify our analytical findings.